Cloud computing as the basis for mobile learning - V. V. Tkachuk (Academy of Cognitive and Natural Sciences, 2013)
Mobile technology in the educational process, mobile learning is no longer new - it is widely used in many educational institutions. Mobile learning offers many advantages: we are free from the institution, schedule, time, geographically. But there are a number of disadvantages that still make it unproductive to work with a mobile device, viz: - limited memory capacity; - The minimal computing power of a mobile device compared to a desktop PC; - limited or backed-down capabilities of editors (text, tabular, etc.); - lack of necessary software for a certain mobile operating system (platform); - limited ability to test and support web applications; - inability to create a virtualized workplace; - lack of ability to install the necessary operating system to test the software product.